Delayed ileal perforation following lollipop-stick ingestion in a two year old - Tareq Swedan; Mohamed Morjan; Mulham Jarjanazi; Nafiza Martini; Alaa Aldin Ismail; Hebatullah Awad; Shamseh Benbash (Journal of Pediatric Surgery Case Reports, 2022)
An ileal perforation caused after ingesting a foreign object is a rare, life-threatening complication that requires surgical intervention. We report a case of ileal perforation in a 2-year-old girl who presented to the pediatric emergency department unconscious with acute abdominal symptoms of unknown etiology 6 months after ingesting a lollipop plastic stick. Her symptoms progressed to shock and loss of consciousness over one day. A laparotomy performed after achieving hemodynamic stabilization was both diagnostic and curative. This is the first reported case of ileal perforation in children due to ingesting a lollipop stick. The hollow interior of the stick may have facilitated the passage of larger amounts of gas into the peritoneum, resulting in the detection of pneumoperitoneum on an erect abdominal film, which is rarely detected on simple abdominal films and may not show up even on computed tomography. The critical presentation of the patient in our case emphasizes the need to consider the often neglected foreign-body-induced perforation as part of the differential diagnosis and to recognize the characteristic early signs and symptoms of deterioration. Furthermore, the importance of comprehensive history taking, which includes a serious investigation of any previous incidents of foreign body ingestion, cannot be overstated.